The methodology of THz-VIS fused images evaluation - Kowalski, Marcin; Piszczek, Marek; Palka, Norbert; Szustakowski, Mieczyslaw (Photonics Letters of Poland, 2013)
Image fusion can be used in a wide range of security applications for example detection and identification of hidden objects. Our goal is to build a system harmless to humans for screening and detection of hidden objects using a THz camera. A very important aspect of applying various processing techniques to images is proper assessment of image quality. We propose a combination of two image quality assessment methods as a methodology of assessing quality of the fused images and a method to compare image fusion algorithms. Full Text: PDF References V. A. Trofimov et al., "Possible way for increasing the quality of imaging from THz passive device", Proc. SPIE 8189 (2011). CrossRef M. Piszczek, M. Kowalski, M. Szustakowski, "Measurement Stand for TeraEYE Inspection", Acta Phys. Pol. A 120, 720-724 (2011). DirectLink ThruVision System Ltd. DirectLink C. Toxqui-Quitl et al., "Multifocus image fusion using the Haar wavelet transform", Proc. SPIE 5558 (2004). CrossRef M. Kowalski, M. Piszczek, N. Palka, M. Szustakowski, "Processing of THz images acquired by passive camera", Phot. Lett. Poland 4(3) 97-99 (2012). DirectLink N. N. Wang, J. H. Qiu, W. B. Deng, "Development status of millimeter wave imaging systems for concealed detection", Infrared Technology 31, N3, 129-135 (2009). DirectLink M. Sumathi, R. Barani, "Qualitative evaluation of pixel level image fusion algorithms", Proc. of IEEE, PRIME, 312-317 (2012). CrossRef W. Pei, G. Wang, X. Yu, "Performance evaluation of different references based image fusion quality metrics for quality assessment of remote sensing Image fusion", Proc. of IEEE, IGARSS, 2280-2283 (2012). CrossRef D. Brunet, E. R. Vrscay, Z. Wang, "On the Mathematical Properties of the Structural Similarity Index", IEEE Trans. on Image Proc. 21(4), 1488-1499 (2012). CrossRef Z. Wang, A. Bovik, "Image quality assessment: from error visibility to structural similarity", IEEE Trans. on Image Proc 13 (4), 600-612 (2004). CrossRef A. Mittal, R. Soundararajan, A. C. Bovik, "Making a ?Completely Blind? Image Quality Analyzer", IEEE Sig. proc. Lett. 20, 209-212 (2013). CrossRef